2017
DOI: 10.1111/his.13273
|View full text |Cite
|
Sign up to set email alerts
|

Atypical intraductal proliferation and intraductal carcinoma of the prostate on core needle biopsy: a comparative clinicopathological and molecular study with a proposal to expand the morphological spectrum of intraductal carcinoma

Abstract: AIP represents a lower-grade morphological spectrum of IDC-P, associated with intermediate-risk PCa. Patients with only AIP need an immediate repeat biopsy to rule out clinically significant PCa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
0
4

Year Published

2018
2018
2019
2019

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 30 publications
2
57
0
4
Order By: Relevance
“…Table 2 summarizes the frequency of each nine epithelial features and two tumor stroma characteristics and its association with PTEN loss. Of 9 epithelial and 2 tumor stroma features of PCa analyzed, "small well-formed glands" pattern was most frequent (91%), followed by "poorly formed glands" (58%), IDC-P (31%) (Figure 1 PTEN loss observed for IDC-P in this study is consistent with that reported in previous studies analyzing the molecular features of IDC-P. 29,30 In a recent study, comparing molecular features of atypical intraductal proliferation and IDC-P in prostate biopsies, we demonstrated that PTEN loss was present in over 72% of IDC-P. 30 In addition, PTEN loss is concordant with the invasive carcinoma component in over 90% of cases. 31 Recent studies have shown that loss of cytoplasmic PTEN is associated with IDC-P, but not with HGPIN.…”
Section: Frequency Of Pten Loss Pca and Correlation With Ggsupporting
confidence: 88%
See 3 more Smart Citations
“…Table 2 summarizes the frequency of each nine epithelial features and two tumor stroma characteristics and its association with PTEN loss. Of 9 epithelial and 2 tumor stroma features of PCa analyzed, "small well-formed glands" pattern was most frequent (91%), followed by "poorly formed glands" (58%), IDC-P (31%) (Figure 1 PTEN loss observed for IDC-P in this study is consistent with that reported in previous studies analyzing the molecular features of IDC-P. 29,30 In a recent study, comparing molecular features of atypical intraductal proliferation and IDC-P in prostate biopsies, we demonstrated that PTEN loss was present in over 72% of IDC-P. 30 In addition, PTEN loss is concordant with the invasive carcinoma component in over 90% of cases. 31 Recent studies have shown that loss of cytoplasmic PTEN is associated with IDC-P, but not with HGPIN.…”
Section: Frequency Of Pten Loss Pca and Correlation With Ggsupporting
confidence: 88%
“…Of all 88 PCa cases with PTEN loss, IDC‐P was present in 61 (69%), compared to 20 (12%) of cases with intact PTEN ( P < 0.001). The high frequency of PTEN loss observed for IDC‐P in this study is consistent with that reported in previous studies analyzing the molecular features of IDC‐P . In a recent study, comparing molecular features of atypical intraductal proliferation and IDC‐P in prostate biopsies, we demonstrated that PTEN loss was present in over 72% of IDC‐P .…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…To our knowledge, this is the first study to report PTEN loss in RP specimens without any invasive disease (cases 3 and 4). In contrast to ERG, which is not infrequently expressed in HGPIN as an early event in PCa pathogenesis [10,45], PTEN loss is rarely observed in HGPIN, with one of our prior studies showing no PTEN loss in HGPIN lesions [20] and one study reporting PTEN loss in only one instance of HGPIN [46]. As discussed previously, PTEN loss in HGPIN occurs in the setting of retrograde spread of invasive carcinoma, but in cases without any concomitant invasive disease, no PTEN loss in HGPIN has been reported [47].…”
Section: Discussionmentioning
confidence: 67%